Aneurysm of the Common Iliac Artery Revealing a Behcet's Disease - Elqatni M.; Fatihi J.; Elomri N.; Jira M.; Sekkach Y.; Amezyane T.; Ennibi K.; Abouzahir A. (Journal of Hypertension and Cardiology, 2020)
A case report of a common iliac artery aneurysm revealing underlying Behçet’s disease. It reviews diagnostic clues, vascular complications, and multidisciplinary management.
Keywords: hypertension